A comparative analysis of subsidized and non-subsidized relative child care in Kansas - Curry, Susan Elizabeth Willard (Kansas State University, 2011)
Positive child outcomes are related to high quality child care environments as evidenced through longitudinal studies (Campbell, Ramey, Pungello, Sparling, & Miller-Johnson, 2002; The National Institute of Child Health and Human Development [NICHD] Early Child Care Research Network, 2005; Schweinhart, Montie, Xiang, Barnett, Belfield, & Nores, 2005). These findings are important particularly for young children from low-income families. As these children are commonly the recipients of child care by a relative, high quality relative care is essential (U. S. Census Bureau, 2005; Brown-Lyons, Robertson, & Layzer, 2001; Collins & Carlson, 1998; Ehrle, Adams, & Tout, 2001). Prior research on the quality of care provided by relatives has been limited, inconsistent, and inconclusive due to differing methodological approaches. Previous studies have often grouped relative child care providers along with other home-based care settings; however, they are not the same. Previous studies have also employed a variety of measurement tools to assess quality. This study examined the overall quality of care in relative child care settings using a tool specifically designed for relative child care, comparing the quality of care and motivations for care between subsidized and non-subsidized settings. Overall, findings were consistent with results of previous studies on kith and kin or relative child care providers in that 1) a wide range of quality of care was observed among both subsidized and non-subsidized settings; 2) no differences were observed between quality in subsidized and non-subsidized; 3) no differences were observed between quality of care based on motivation for providing care. The majority of providers will provide care for family regardless of availability of payment; however, subsidized providers were more family-oriented in their motivation compared to non-subsidized who more child-oriented. While all levels of care were observed in both infant/toddler and preschool settings, infant/toddler settings scored higher on all adult-child interaction variables. These settings were also observed to be safer than preschool settings. Also subsidy status alone does not necessarily increase or affect quality of the care as payment is not the primary motivation for care. Policymakers should, therefore, explore other means by which to enhance quality such as equitable subsidy rates across home-based settings and support programs for this population.
Keywords: Relative child care; Child care assessment tool for relatives; Child care quality; Child care subsidy; Early Childhood Education (0518)